Perspektif Hukum Pidana Terhadap Tindak Pidana Cyber Pornography Dalam Penggunaan Platform OnlyFans - Ferreira, Francisca Das Dores; Manafe, Deddy R. CH.; Dima, Adrianus Djara (Artemis Law Journal, 2025)
Technological advancements, especially in the internet and social media, have significantly impacted human life. In Indonesia, cyber pornography has become a growing concern, particularly through platforms like OnlyFans. Although such content is punishable under Indonesian criminal law, law enforcement in the digital space remains weak due to various challenges. This makes it essential to understand and address the misuse of digital platforms to prevent further spread of pornographic material. The problem formulation in this study focuses on the misuse of OnlyFans for cyber pornography, which violates Indonesian law. Although the platform is officially blocked by Kominfo, it is still accessible via VPN, allowing the illegal distribution of content. Under the ITE Law and the Criminal Code, individuals who intentionally share or profit from pornographic content may face imprisonment and fines. Therefore, stronger legal enforcement and increased public awareness are urgently needed. This research uses a normative juridical approach, combining qualitative analysis and legislative review. The study is based on secondary legal materials, analyzed through a descriptive method. The findings reveal that OnlyFans facilitates paid transactions between creators and fans for pornographic content. Despite being blocked, access via VPN continues. Current laws and government measures are insufficient to address technological developments, especially regarding OnlyFans. Effective legal action requires better technological understanding and greater public awareness. The study concludes that various motivations drive the use of OnlyFans for pornography, which can potentially lead to further criminal acts under Indonesian law.